Residential Construction Site Selection Through Interval-Valued Hesitant Fuzzy CODAS Method - Karasan, Ali; Zavadskas, Edmundas Kazimieras; Kahraman, Cengiz; Keshavarz-Ghorabaee, Mehdi (VILNIUS UNIV PRESS, 2019)
Construction site selection is a complex problem involving many alternatives and conflicting criteria with vague and imprecise evaluations. Fuzzy multi-criteria decision-making methods are the most effective tools to obtain optimum solutions under possibilistic uncertainty. In this paper, a novel interval hesitant fuzzy CODAS method is proposed and applied to a residential construction site selection problem. A comparative analysis with ordinary fuzzy CODAS method is applied for validating the proposed method. Also, a sensitivity analysis is conducted for the stability of the ranking results of the interval hesitant fuzzy CODAS method. The results of the analyses demonstrate the effectiveness of our proposed method.
Keywords: construction site; multi-criteria; CODAS; hesitant fuzzy sets; selection problem; ANALYTIC HIERARCHY PROCESS; WASTE INCINERATION PLANT; DECISION-MAKING; CRITERIA; AHP; CITY; Computer Science; Mathematics